(3HOGjGJ GdeTGjNs - (3eMeO Hf GdMSjf Hf eMeO Hf ehSi GdCROj GdSdej GdfjSGHhQj, CHh YHO GdQMef,J (B412 (3g` s ((3ESMGb Hf eMehO Hf HGchjI s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO abO SFdJ ai LeY TF ef eHGOF GdeTGjN hChGFd CMhGdge , heG CcQe Gddg YR hLd Hg eJCNQi eTGjNge s
(3BNQgG (B:s
(3bGd GdCSJGP GdEeGe CHh GdbGSe (B: (3agPg hUdJfG Edi GdeQjOjf hbO fLR dfG EedGA gPg GdQSGdI ai ChGFd SfI KeGf hKdGKjf hCQHYeGFI hGdMeO ddg QH GdYGdejf h, hUdi Gddg Ydi SjOfG eMeO hBdg hCUMGHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3heYg JYQjaGJ UhajI ddEeGe CHh GdbGSe YHO GdcQje Hf ghGRf GdbTjQis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B258s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs